Hasyim Asy'ari's Dimensions of Multicultural Spiritual Leadership: Harmony in Education and Society in Indonesia - Suhendi, Saca; Khoiruddin, Heri; Ihsan, Mahlil Nurul; Nasir, Tatang Muh; Sain, Zohaib Hassan (LETIGES, 2025)
The spiritual leadership of Hasyim Asy'ari plays an important role in overcoming intolerance, radicalism, and hate speech through moderation (wasathiyah), interfaith dialogue, and strengthening national values ​​such as hubbul wathan minal iman. His leadership transforms conflict into harmony and tolerance by instilling altruistic love and solidarity. This study aims to explain the multicultural spiritual leadership model that combines spiritual values ​​such as faith, altruistic love, and moderation with a multicultural approach that respects religious, cultural, and ethnic diversity. Hasyim Asy'ari's leadership is implemented through the Nahdlatul Ulama organization and Islamic boarding schools, strengthening national unity amid Indonesia's diversity. This study uses a qualitative approach, and the type taken combines phenomenology and literature. Literature studies are focused on studying the thoughts and roles of related figures, while interviews are conducted with lecturers and UIN Sunan Gunung Djati Bandung students. Data are analyzed by filtering important information, coding themes to identify patterns, categorizing based on key dimensions, and synthesizing to find relationships and conclusions. Validation was conducted by cross-checking sources to ensure consistency and avoid bias. The findings show that Hasyim Asy'ari's leadership, shaped by his educational background in Mecca and socio-historical context, created a moderate multicultural leadership model that is still relevant today. This model emphasizes the integration of moral and spiritual values ​​in creating an inclusive society and contributes to the world of education by shaping learning ethics, teacher ethics, and scientific ethics. The originality of this study lies in the analysis of Hasyim Asy'ari's leadership from the perspective of multiculturalism and moral education, which are still rarely studied in depth. However, this study has limitations because it uses a library approach that limits direct empirical data and focuses on the historical context of Indonesia, making it difficult to generalize to other regions.